Analysis of Dynamic Biogas Consumption in Chinese Rural Areas at Village, Township, and County Levels - Gongyi Li; Tao Luo; Jianghua Xiong; Yanna Gao; Xi Meng; Yaoguo Zuo; Yi Liu; Jing Ma; Qiuwen Chen; Yuxin Liu; Yichong Xin; Yangjie Ye (Agriculture)
Understanding the characteristics of biogas demand in rural areas is essential for on-demand biogas production and fossil fuel offsetting. However, the spatiotemporal features of rural household energy consumption are unclear. This paper developed a rural biogas demand forecasting model (RBDM) based on the hourly loads of different energy types in rural China. The model requires only a small amount of publicly available input data. The model was verified using household energy survey data collected from five Chinese provinces and one year’s data from a village-scale biogas plant. The results showed that the predicted and measured biogas consumption and dynamic load were consistent. The relative error of village biogas consumption was 11.45%, and the dynamic load showed seasonal fluctuations. Seasonal correction factors were incorporated to improve the model’s accuracy and practicality. The accuracy of the RBDM was 19.27% higher than that of a static energy prediction model. Future research should verify the model using additional cases to guide the design of accurate biogas production and distribution systems.